Overtourism as Urban Overdevelopment: Social Representations and Adaptive Governance in Bali - Putra, I Nyoman Darma; Rosalina, Putu Devi; Nama, I Ketut; Green, Paul; Hitchcock, Michael (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
While numerous studies examine overtourism's mechanisms and impacts, research on how overtourism is perceived and managed within political governance frameworks remains scarce. Using a case study of Bali, Indonesia, this study examines how overtourism is socially and politically constructed through stakeholder interpretations and identifies adaptive strategies to address this narrative. The study employed data triangulation through three key research methods of document analysis of online media, semi-structured interviews, and fieldwork observations across major tourism destinations in Bali. Our findings suggest that overtourism should be treated as an integral component of urban phenomena. We emphasise the importance of socially adaptive strategies focusing on equitable distribution, aligned with public trust in government through transparency and credibility. Through recognition of long-term tourists' impact, our findings complicate the association of overtourism with lifestyle migrants. The study contributes to reimagining overtourism as a conjoint urban phenomenon and encourages policymakers to advance towards comprehensive urban planning.
Keywords: overtourism; social representation theory; adaptive management strategies; Bali; urbanisation; migration